INTEGRASI STRUKTUR DAN FUNGSI BAGIAN TUMBUHAN DENGAN BAYANI, BURHANI, ‘IRFANI DI SDIT BUNAYYA - Asriana Harahap; Syarifuddin Harahap (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractPlants are living things that do not experience the activity of moving like humans and animals, but they can reproduce in their own way. The parts that are in plants are always different from one another, this is influenced by climatic factors and geographic areas. Areas that have lots of sunlight will be different from plants that live in areas with cool weather or below 20 degrees Celsius. Based on the issues that have developed in education during this decade, this paper will try to develop science material on